The Kuntulan Art of the Cendono Arum Group in Banyuanyar Village, Banyuwangi Regency: A Study of Performance Forms and Functions - Donna Mirza Zamzama Salsabilla (Universitas Negeri Surabaya, 2026)
Cendono Arum is a traditional kuntulan art group based in Banyuanyar Village, Kalibaru Subdistrict, Banyuwangi Regency. The group’s uniqueness lies in its use of the Madurese language in the lyrics of its marching songs, which reflect the everyday language of the local community. Additionally, its performance style—which incorporates innovations in musical arrangements, costumes, stage design, and lighting—is a major draw for audiences. This study aims to examine the performance style and the social and cultural functions of the Cendono Arum Kuntulan performance. The research employs a qualitative method with data collection techniques including observation, interviews, and documentation. These data collection techniques were conducted directly by the researcher to obtain comprehensive data. The data were analyzed through the stages of data collection, reduction, and presentation. The results of the study indicate that Cendono Arum performances serve not only as entertainment but also as a medium for cultural preservation, a reinforcement of local identity, and a means of building social relationships within the community. The existence of this group demonstrates that traditional art remains relevant and plays a vital role in the local community.